A diverse ichnofauna and its palaeoenvironmental significance from the Upper Jurassic Argiles de Saïda Formation (Northwestern Algeria). (3rd April 2022) - Cherif, Amine; Naimi, Mohammed Nadir
ABSTRACT: Forty-three ichnospecies belonging to 30 ichnogenera are described from the Upper Jurassic Argiles de Saïda Formation (north-western Algeria), which consists of mixed shallow marine siliciclastic-carbonate sediments. The ichnological analysis reveals that the majority of the ichnoassemblages are represented by non-graphoglyptid traces dominated by Bergaueria isp., Ophiomorpha isp., O . rudis, Neonereites biserialis, N . triserialis . Furthermore, Chondrites isp., Palaeophycus isp., Phycosiphon isp., Planolites isp., Protovirgularia isp., Scolicia isp. and Thalassinoides isp. are common ichnotaxa. Ancorichnus isp., Archaeonassa isp., Gordia isp., Helminthoidichnites isp., Helminthopsis isp., Nereites isp., Ophiomorpha annulta, Oravaichnium isp., Oravaichnium hrabei, Protovirgularia dichotoma, Rutichnus rutis, Thalassinoides suevicus are rare, whereas, Chondrites targionii, Nereites irregularis, Neonereites uniserialis, Ptychoplasma excelsum, Spongeliomorpha isp., Taenidium isp., Taenidium serpentinum, ? Tubulichnium isp. and Zoophycos isp. are rare to scarce ichnotaxa. The graphoglyptid assemblage has very low diversity with only three ichnotaxa which are Megagrapton isp., Megagrapton submontanum and Scolicia strozzii . The described ichnoassemblages are assigned to the Cruziana to Cruziana-Nereites ichnofacies transition.